Appropriate Use of Electrochemical Impedance Spectroscopy in Water Splitting Electrocatalysis. Issue 10 (25th May 2020) - Anantharaj, Sengeni; Noda, Suguru
Abstract: Electrochemical impedance spectroscopy (EIS) is an efficient tool that reveals the electrochemical characteristics of catalysts, surfaces, interfaces, coatings, and so forth. Use of EIS in different areas of energy research wherever current, potential, and charge determine the performance has become inevitable. Electrocatalytic water splitting is one of such fields focused on generating high purity hydrogen, where EIS is used to correlate the activity trends measuring charge transfer resistances ( R ct ). In doing so, different conventions are followed. A few perform EIS at the open circuit potential (OCP), a few perform at onset potential or at a potential before onset potential, a few perform at different potentials for different catalysts at which they deliver the same current density, and a large group of people choose a constant potential beyond onset, at which all the studied catalysts show appreciable catalytic activity. Existence of such different practices in using EIS to characterize water splitting electrocatalysts often lead to misinterpretation of the activity trends. Hence, to provide a clear view on the appropriate use of EIS in water splitting electrocatalysis, we have carried out a comparative EIS study on the oxygen evolution reaction (OER) activity trend of stainless steel 304 (SS‐304), Co, Ni, and Cu foils in 1 M KOH at all the above‐stated conditions and the results showed that the EIS carried out at constant potentials in the catalytic turnover region is appropriate. Abstract : Deciphering the ambiguity : There exists an ambiguity among researchers in electrochemical water splitting about the appropriate use of electrochemical impedance spectroscopy (EIS). This article vindicates this ambiguity studying catalytically different metals at different set potentials.